2022
DOI: 10.3390/biom12070861
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic Analysis Predicts a Novel Genetic Module Related to Triple Gene and Binary Movement Blocks of Plant Viruses: Tetra-Cistron Movement Block

Abstract: Previous studies have shown that the RNA genomes of some plant viruses encode two related genetic modules required for virus movement over the host body, containing two or three genes and named the binary movement block (BMB) and triple gene block (TGB), respectively. In this paper, we predict a novel putative-related movement gene module, called the tetra-cistron movement block (TCMB), in the virus-like transcriptome assemblies of the moss Dicranum scoparium and the Antarctic flowering plant Colobanthus quite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Our analysis revealed that a number Reclovirids encode non-replicative proteins with other types of putative zinc-finger motifs. In particular, the ORF2 protein of Atriplex prostrata VLRA (Supplementary Table S1) contains the hexa-cysteine motif C(X6)C(X)C(XX)CXC(X12)C, which resembles unconventional hexa-cysteine motifs like those found in proteins of Hepatitis virus E and viruses of the genus Pestivirus [16,17], and in the small protein encoded by the ORF preceding TCMB in Colobanthus quitensis VLRA [7].…”
Section: Protein Domains and Motifs In Non-replicative Proteins Of Re...mentioning
confidence: 99%
See 2 more Smart Citations
“…Our analysis revealed that a number Reclovirids encode non-replicative proteins with other types of putative zinc-finger motifs. In particular, the ORF2 protein of Atriplex prostrata VLRA (Supplementary Table S1) contains the hexa-cysteine motif C(X6)C(X)C(XX)CXC(X12)C, which resembles unconventional hexa-cysteine motifs like those found in proteins of Hepatitis virus E and viruses of the genus Pestivirus [16,17], and in the small protein encoded by the ORF preceding TCMB in Colobanthus quitensis VLRA [7].…”
Section: Protein Domains and Motifs In Non-replicative Proteins Of Re...mentioning
confidence: 99%
“…It also contains a recently described group of "Tetra-cistron movement block (TCMB)-containing viruses" (Tecimovirids) coding for the TCMB movement gene module instead of the triple gene block (TGB) of movement genes found in members of the family Benyviridae. [2,7] (Figure 1). The latter branch contains exclusively monopartite viruses and, in particular, includes Goji berry chlorosis virus (GBCV), which encodes six polypeptides and has no close relatives with similar genome organization [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virus-like sequences are often found in plant transcriptomes, as plant tissue samples collected for new-generation sequencing may have been obtained from virus-infected plants [ 15 ]. Another TGB-related gene module, the “tetra-cistron movement block” (TCMB), has recently been discovered in the transcriptomic contigs of the moss Dicranum scoparium and the flowering plant Colobanthus quitensis ; these contigs correspond to a genomic segment, termed RNA2, of novel viruses with two-component RNA genomes provisionally assigned to the Tecimovirids group related to the family Benyviridae [ 16 ]. Sequence analysis indicates that the second TCMB gene encodes a helicase domain-containing protein related to TGB1 and BMB1, whereas the proteins encoded by the third and fourth TCMB genes are similar to TGB2 and TGB3, respectively [ 14 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another TGB-related gene module, the “tetra-cistron movement block” (TCMB), has recently been discovered in the transcriptomic contigs of the moss Dicranum scoparium and the flowering plant Colobanthus quitensis ; these contigs correspond to a genomic segment, termed RNA2, of novel viruses with two-component RNA genomes provisionally assigned to the Tecimovirids group related to the family Benyviridae [ 16 ]. Sequence analysis indicates that the second TCMB gene encodes a helicase domain-containing protein related to TGB1 and BMB1, whereas the proteins encoded by the third and fourth TCMB genes are similar to TGB2 and TGB3, respectively [ 14 , 16 ]. Interestingly, the protein encoded by the fourth TCMB gene also shows similarity to TGB2, suggesting that the 5′-distal gene in TGB and TCMB may have originated by a duplication of the TGB2/BMB2 gene of an ancestral BMB-like gene module [ 14 ].…”
Section: Introductionmentioning
confidence: 99%